Improvement of specific capacity of lithium iron phosphate battery by increasing the surface area and electrical conductivity of cathode electrode using graphene foam - KOKMAT, Phurida; MATSAYAMAT, Patiphat; WONGRACH, Kunaree; SURINLERT, Piyaporn; RUAMMAITREE, Akkawat (Journal of Metals, Materials and Minerals, 2023)
Lithium iron phosphate (LFP) is widely used as an active material in a cathode electrode for lithium-ion batteries (LIBs). LFP has many remarkable properties such as high working voltage and excellent thermal stability. However, it suffers with slow ion diffusion and low electrical conductivity. Graphene foam has many outstanding properties such as large surface area and great electrical conductivity. These properties are suitable for improving the cathode electrode. In this work, the graphene foam was synthesized by chemical vapor deposition. The cathode electrode was prepared by dropping the LFP on the graphene foam. We found that the specific capacity of battery which contained the LFP between the anode and the graphene foam (LFP/GF) was 23.1 mAh⸳g-1 at 3C, while the specific capacity of battery which contained the graphene foam between the anode and the LFP (GF/LFP) was 112.6 mAh⸳g-1 at 3C. The diffusion coefficients of Li+ of GF/LFP was 9.1 times higher than that of LFP/GF. The specific capacity of GF/LFP was higher than that of LFP/GF at high current density due to the high ion transfer rate which arises from the graphene foam.